2020
DOI: 10.1016/j.ijcha.2020.100661
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation for atrial fibrillation in a low-volume center using contemporary technology

Abstract: Highlights There has been significant heterogeneity in the definition of what constitutes as low volume operator /center for AF ablation. Current literature suggests lower success rates but higher complications rates in low-volume centers. First AF catheter ablation in a low-volume center has comparable safety and efficacy outcomes to high-volume centers using contemporary ablation technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(50 reference statements)
0
0
1
Order By: Relevance
“…9 Although there was one study reported a success rate of AF ablation in a low-volume center with 19.5% recurrence of paroxysmal AF in one year and 23.8% recurrence of persistent AF in one year, this study could not be compared directly to our cohort due to different AF ablation technique and method of obtaining data. 10 There are several interesting points in our study that are different from the studies from Western countries.…”
Section: Discussioncontrasting
confidence: 71%
“…9 Although there was one study reported a success rate of AF ablation in a low-volume center with 19.5% recurrence of paroxysmal AF in one year and 23.8% recurrence of persistent AF in one year, this study could not be compared directly to our cohort due to different AF ablation technique and method of obtaining data. 10 There are several interesting points in our study that are different from the studies from Western countries.…”
Section: Discussioncontrasting
confidence: 71%